2010
DOI: 10.1038/aja.2010.76
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes and oxidative stress: dilemma for sperm function and male fertility

Abstract: Spermatozoa are constantly exposed to the interphase between oxidation through high amounts of reactive oxygen species (ROS) and leukocytes, and reduction by means of scavengers and antioxidants. Considering the very special functions as being the only cells with such high polarization and exerting their functions outside the body, even in a different individual, the female genital tract, the membranes of these cells are chemically composed of an extraordinary high amount of polyunsaturated fatty acids. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(150 citation statements)
references
References 155 publications
2
134
0
14
Order By: Relevance
“…They further stated that the concentration of vitamin C supplements is of importance because a high concentration of vitamin C could act as a reducing agent and interfere with the disulfide bonds between the protamines. Such paradoxes are called the 'antioxidant paradox' (reviewed in [Henkel 2011]). This study revealed a positive correlation between the percentage of cytoplasmic (DCF + sperm) and mitochondrial (R123+ sperm) ROS with sperm viability and motility.…”
Section: Discussionmentioning
confidence: 99%
“…They further stated that the concentration of vitamin C supplements is of importance because a high concentration of vitamin C could act as a reducing agent and interfere with the disulfide bonds between the protamines. Such paradoxes are called the 'antioxidant paradox' (reviewed in [Henkel 2011]). This study revealed a positive correlation between the percentage of cytoplasmic (DCF + sperm) and mitochondrial (R123+ sperm) ROS with sperm viability and motility.…”
Section: Discussionmentioning
confidence: 99%
“…64 The presence of leukocytes on the sperm surface and the similarity of their cellular mechanisms for superoxide generation to those of activated spermatozoa could explain the decrease in superoxide anion generation in spermatozoa. 65,66 It is believed that leukocytes and spermatozoa share a similar mechanism for ROS generation: an NADPH oxidase located in or near the cell membrane. 67 Although controversy exists regarding the form of this enzyme, 68 exogenous gangliosides undeniably decrease the extracellular production of superoxide radicals.…”
Section: Gangliosides and Spermatozoamentioning
confidence: 99%
“…However, if achieving the correct balance between oxidation and reduction were so simple, then antioxidants would be routinely included in all semen diluents. The reason this does not occur is that uncontrolled antioxidant treatment can also be detrimental, as cells generally function in a reduced state (termed the 'anti-oxidant paradox'; reviewed by Henkel (2011)). For instance, capacitation is reduction dependent and it is not clear whether excessive anti-oxidant protection during sperm handling renders the surviving cells responsive to a capacitation-inducing environment.…”
Section: Stabilisation Of the Sperm Surface With Cholesterol And Othementioning
confidence: 99%